N6-cyclopentyladenosine inhibits proliferation of murine haematopoietic progenitor cells in vivo - Pospísil, Milan; Hofer, Michal; Vacek, Antonín; Holá, Jirina; Pipalová, Iva; Znojil, Vladimír (European journal of pharmacology, 2005)
Effects of N6-cyclopentyladenosine (CPA), the selective adenosine A1 receptor agonist, on bone marrow haematopoietic progenitor cells for granulocytes and macrophages (CFC-GM) were investigated by utilizing the model of haematopoietic damage induced by 5-fluorouracil. Experiments were performed in vivo on B10CBAF1 mice. A single i.p. injection of CPA at the optimum dose of 200 nmol/kg administered 22 h before a single injection of 5-fluorouracil (100 mg/kg, i.p.) protected CFC-GM against the cytotoxic damage as determined 4 days later. Isomolar doses of the selective agonists for adenosine A2A receptors, i.e. 2-p-(2-carboxyethyl)-phenethylamino-5'-N-ethylcarboxamidoadenosine, and for adenosine A3 receptors, i.e. N6-(3-iodobenzyl)adenosine-5'-N-methyluronamide, did not induce such effects. Because 5-fluorouracil is a cell cycle-specific drug damaging mainly cells in the S-phase, protective effects of CPA can be explained by its inhibitory action on the cell cycling. This interpretation was confirmed by experiments demonstrating that repeated administration of CPA in the hyperproliferation phase of the recovering haematopoiesis after 5-fluorouracil treatment inhibited transiently restoration of CFC-GM counts.
Keywords: Cell Proliferation; hematopoetické kmenové buňky; Mice; zvířata; adenosin; mužské pohlaví; proliferace buněk; inhibitory růstu; myši inbrední CBA; Growth Inhibitors; Mice, Inbred CBA; myši; Dose-Response Relationship, Drug; Hematopoietic Stem Cells; Animals; vztah mezi dávkou a účinkem léčiva; Mice, Inbred C57BL; Adenosine; Male; myši inbrední C57BL